Disaster Resilience and Preparedness Program Evaluation for Enhancement (International Journal of Scientific Research and Management (IJSRM), 2023)
The study was conducted to evaluate the level of disaster resilience and preparedness among the members of the MDRRMC and BDRRMC in the Municipality of Alabel, Sarangani Province. Descriptive-correlative research design were utilized employing quantitative method. Data were gathered through survey questionnaires administered to 219 respondents. Key Informant Interviews were conducted among 9 members of the BDRRMC to triangulate the quantitative data. The gathered data were analyzed using frequency, percentage, weighted mean, and Pearson correlation. The findings of the study revealed that there was a proportional number of male and female respondents of which majority of them belong to adult aged group. Majority of the respondents are government employees and government officials who are college graduates. The level of disaster resilience of the respondents in terms of the five areas on governance, risk assessment, knowledge and education, risk management and vulnerability reduction, and disaster preparedness and response are relatively high with a verbal description of high resilience. On the level of disaster preparedness among the respondents, the results revealed that the members are always prepared based on the four areas for likelihood of being impacted by a national hazard, vulnerability of physical structures, people, and livelihoods, barangay-level planning and individual’s preparation for disaster, and individual’s sense of control over their own lives and their ability to participate and influence their community and government. In relation to the disaster resilience and preparedness experiences, three themes emerged in this study as perceived by the informants and these are: (1) Planning and Preparation, (2) Issues and Challenges, and (3) Coping Mechanism. Generally, there is a moderate positive correlation between disaster resilience and disaster preparedness among the respondents (r= .449).